Damage characteristics of recycled aluminium alloys AA6061 undergoing finite strain deformation of tensile loading - Ho, C. S.; Mohd Nor, M. K.; Lajis, M. A.; A. Samad, M. S. (Penerbit UTHM, 2022)
Recycling aluminium alloys has excellent advantages to avoid bad environmental effects while providing significant economic benefits. Many efforts are demanded to identify the appropriate applications, especially in automotive and aerospace fields. It can be observed that various recycling methods have been adopted and examined. However, it is generally agreed that there is still a need for improved recycling methods to fulfil the needs of the required applications as shown by its primary resources. It is a massive challenge and an obvious drawback in such materials due to the degradation of material’s properties related to damage, hence, must be critically analyzed before the potential applications can be identified. Based on this motivation, the present study establishes the effects of temperature and strain rate of hot-forged recycled aluminium alloys AA6061 via uniaxial tensile test implementations. The test is conducted at elevated temperatures of 100°C, 200°C and 300°C, at two different strain rates of 10-4 s -1 and 10-3 s -1 . The tensile behaviour and damage are analyzed in terms of stress-strain curves and microstructural analysis, respectively. The microstructure and fracture surface of such materials are observed using Scanning Electron Microscope (SEM) and Optical Microscope (OM). Generally, the flow stress of recycled AA6061 increases with increasing strain rate and decreases with increasing temperature. The quantity and size of the micro-voids observed is enhanced with the increases in strain rate. It is due to the growth and coalescence of the micro-voids. From the OM analysis, the gap between the grain boundaries become wider with the increases in temperature; thus, the strength of the material decreases.